Relocating gendered violence and anti-genderism within authoritarian populist imagination in Turkey - Yetiş, Erman Örsan (Frontiers in Political Science, 2025)
In Turkey, anti-genderism is significantly influenced by top-down political structures, which are primarily embedded within an authoritarian populist imagination in two distinct yet interconnected ways. Firstly, anti-genderism serves to re-establish the paternalistic social politics characterised by mafia-like tactics. The incumbent regime effectively holds the practical gender needs of women hostage, particularly their need for protection from violence, which is predominantly framed within the context of family-centred policies. Second, it serves to flesh out a masculine understanding of power as a form of masculinist entrenchment, relaying a will-to-power or an insistent desire to maintain power at all costs. Through masculinist entrenchment, the incumbent power normalises the arbitrary use of punitive violence against political dissidents and rivals, and it also attempts to reinforce its image of being potent and invincible amid ongoing economic, political, and social turmoil, adopting an aggressive stance. This paper offers a detailed analytical framework that examines gendered violence, anti-genderism, and authoritarian politics through a relational lens, drawing on various concepts and illustrating their relevance by discussing the case of Turkey. Resisting anti-genderism requires a more comprehensive understanding of gendered violence alongside a transformative political imagination that can potentially reverse the recent authoritarian populist imagination and build a social justice-oriented political framework. To partially achieve this, the paper concludes with a critical discussion through continuum thinking on ways to develop and disseminate such an alternative political imagination across society.